Penerapan Media Permainan Word Square Dalam Pembelajaran Materi Lagu Daerah Kelas V SDN 1 Talang - Novita Nur Afifah; Muhroji Muhroji (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
Student learning outcomes can be divided into three types, namely cognitive learning outcomes related to the material obtained by students, affective learning outcomes related to students' attitudes in carrying out and after the learning process, and student psychomotor learning outcomes related to student skills. The purpose of this study is to determine the application of word square learning media at SDN 1 Talang. The subjects of the study were the principal, teachers and students of SDN 1 Talang. Techniques in data collection namely interviews, observation, and documentation. The results obtained from this study are that SDN 1 Talang has used word square game media in learning, especially folk song material for fifth grade students.